2020
DOI: 10.3389/fmed.2020.547186
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Susceptibility to Antisynthetase Syndrome Associated With Single-Nucleotide Variants in the IL1B Gene That Lead Variation in IL-1β Serum Levels

Abstract: The antisynthetase syndrome (ASSD) is an autoimmune disorder characterized by myositis, arthritis, mechanic's hands, fever, Raynaud phenomenon, and interstitial lung disease (ILD). We aimed to evaluate single-nucleotide polymorphisms in the interleukin 1B (IL1B) gene and their association between ILD with antisynthetase autoantibodies, as well as IL-1β serum levels. The most frequent antisynthetase autoantibody was anti-Jo1. The most frequent tomographic pattern was non-specific interstitial pneumonia, whereas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…We must identify the reason why IL-1β level is high only in certain sCAEBV patients. It is reported that single nucleotide polymorphisms (SNPs) of IL-1β, rs16944, and rs1143627, are related to IL-1β serum levels in patients of febrile seizure ( Choi et al, 2019 ) and antisynthetase syndrome ( Ponce-Gallegos et al, 2020 ). Interestingly, these SNPs contribute to increasing the risk of coronary artery lesions in Kawasaki disease ( Fu et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…We must identify the reason why IL-1β level is high only in certain sCAEBV patients. It is reported that single nucleotide polymorphisms (SNPs) of IL-1β, rs16944, and rs1143627, are related to IL-1β serum levels in patients of febrile seizure ( Choi et al, 2019 ) and antisynthetase syndrome ( Ponce-Gallegos et al, 2020 ). Interestingly, these SNPs contribute to increasing the risk of coronary artery lesions in Kawasaki disease ( Fu et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the IL1B gene SNPs (rs1143643 and rs1143627) chosen in our study have been demonstrated to be associated with other autoimmune inflammatory diseases, such as RA ( Rong et al, 2020 ), ASSD ( Ponce-Gallegos et al, 2020 ) and inflammatory bowel disease (IBD) ( Liu et al, 2020 ). In view of the potential role of IL1B rs1143627 and rs1143643 in the immune and inflammatory-related diseases mentioned above and the fact that relationships between polymorphisms in the IL1B gene and the risk of T1DM remain discrepant, we aimed to investigate whether the presence of these two polymorphisms (rs1143627 and rs1143643) is associated with T1DM.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, attention has been given to the role of IL1B in the pathogenesis of autoimmune and inflammatory diseases. Numerous studies have demonstrated that there are gene variations and polymorphisms in the IL1B gene and that these variants could influence the transcription and expression of the IL1B gene and are specifically correlated with many autoimmune and inflammatory diseases, including systemic lupus erythematosus (SLE) ( Mohammadoo-Khorasani et al, 2016 ), antisynthetase syndrome (ASSD) ( Ponce-Gallegos et al, 2020 ), rheumatoid arthritis (RA) ( Hu et al, 2020 ) and primary progressive multiple sclerosis ( Malhotra et al, 2020 ). Nevertheless, whether there is a relationship between the IL1B gene and T1DM susceptibility has not been reported before.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, previous studies have tried to identify genetic susceptibility for ASSD or IIM-related ILD with inconclusive results. Our research group recently described that the rs1143634/GG genotype of the IL1B gene is associated with a higher risk for ASSD in a Mexican mestizo population [ 30 ]. Sugiura et al [ 31 ] showed that STAT4 rs7574865 is associated with DM/PM, as well as ILD-related myopathies in a Japanese population, suggesting that DM/PM with or without ILD shares a common gene associated.…”
Section: Discussionmentioning
confidence: 99%
“…Sugiura et al [ 31 ] showed that STAT4 rs7574865 is associated with DM/PM, as well as ILD-related myopathies in a Japanese population, suggesting that DM/PM with or without ILD shares a common gene associated. In a Chinese population, Chen and coworkers [ 30 ] described two SNPs rs7117932 and rs6590330 in the ETS1 , and the rs951005 in CCL21 might confer genetic IIM predisposition, as well as IIM-ILD. Conversely, ANKRD55 SNP rs7731626 was a protective factor for DM/PM-ILD in the Chinese Han population [ 32 ].…”
Section: Discussionmentioning
confidence: 99%